1981
DOI: 10.4095/119430
|View full text |Cite
|
Sign up to set email alerts
|

Part 2, Conodont biostratigraphy and paleoecology of the Ellis Bay formation, Anticosti Island, Quebec, with special reference to late ordovician-early silurian chronostratigraphy and the systematic boundary

Abstract: The Ellis Bay Formation on Anticosti Island, Quebec, is subdivided into six members and is composed of calcareous shale and argillaceous limestone and varies in thickness from 53 m in the west to about 96 m in the east. Member 6 accounts for about half the total thickness of the formation and near its base small bioherms are developed widely across the island. Lateral variation in lithology represents a gradual transition from a nearshore facies (east) to an offshore, shallow subtidal facies (west) . The membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…The biostratigraphical assignment based on conodonts is in good agreement with evidence from the graptolites in the strata just below the conodont-bearing interval (Rickards et al 1996). Similar faunas of the D. kentuckyensis Biozone are present in the Lower Silurian successions of Michigan and Ontario (Pollock, Rexroad & Nicoll, 1970), Ohio and Kentucky (Rexroad, 1967;Cooper, 1975Cooper, , 1980Rexroad & Kleffner, 1984), Member 6 of the Ellis Bay Formation, Anticosti Island, Quebec (Fåhraeus & Barnes, 1981;McCracken & Barnes, 1981), the Northwest Territories (McCracken, 1981), British Columbia (McCracken, 1981 and the Lower Llandovery of Estonia (P. Männik, unpub. Dissertationes Geologicae, Univ.…”
Section: B Stratigraphic and Palaeogeographic Significancesupporting
confidence: 58%
See 2 more Smart Citations
“…The biostratigraphical assignment based on conodonts is in good agreement with evidence from the graptolites in the strata just below the conodont-bearing interval (Rickards et al 1996). Similar faunas of the D. kentuckyensis Biozone are present in the Lower Silurian successions of Michigan and Ontario (Pollock, Rexroad & Nicoll, 1970), Ohio and Kentucky (Rexroad, 1967;Cooper, 1975Cooper, , 1980Rexroad & Kleffner, 1984), Member 6 of the Ellis Bay Formation, Anticosti Island, Quebec (Fåhraeus & Barnes, 1981;McCracken & Barnes, 1981), the Northwest Territories (McCracken, 1981), British Columbia (McCracken, 1981 and the Lower Llandovery of Estonia (P. Männik, unpub. Dissertationes Geologicae, Univ.…”
Section: B Stratigraphic and Palaeogeographic Significancesupporting
confidence: 58%
“…(1) Severnava Zemlya (Männik, 1983); (2) North Greenland (Armstrong, 1990); (3) (Rexroad & Craig, 1971); (6) Michigan and Ontario (Pollock, Rexroad & Nicoll, 1970); Kentucky and Ohio (Rexroad & Nicoll, 1972, Rexroad, 1967); (7) Gaspé Peninsula (Nowlan, 1981); Anticosti Island (Nowlan & Barnes, 1981, McCracken & Barnes, 1981; (8) Oslo region, Norway (Aldridge & Mohamed, 1982); southern Sweden (Bergström & Bergström, 1996); Estonia (Männik, 1992); Poland (Männik & Malkowski, 1998); (9) western Argentina (this study); (10) Sahara, northern Africa (Remack-Petitot, 1960); (11) Cantabrian Mountains of northern Spain Pyrenees (Sanz & Sarmiento, unpub. data cited in García-López et al 1994).…”
Section: Systematic Palaeontologymentioning
confidence: 98%
See 1 more Smart Citation
“…The first occurrence of O. hassi [and/or O. oldhamensis (Rexroad, 1967)] was considered to be indicative of the Ordovician-Silurian boundary by McCracken and Barnes (1981), and O. hassi is the nominate species of the lowest Llandovery biozone from Anticosti Island (Zhang and Barnes, 2002), as well as from Sweden . Bergström et al (2012) reported occurrences of O. hassi in the latest Ordovician, across the Ordovician-Silurian boundary, and into the Telychian.…”
Section: Resultsmentioning
confidence: 99%
“…McCracken and Barnes 1981 from Anticosti Island, Quebec) extend the stratigraphic range back to near the base of the Silurian System, but the species has not been reported from Telychian strata. The geographical range of 1. dejectu extends through eastern Canada (Fihraeus and Barnes 1981;McCracken and Barnes 1981;Nowlan 1981Nowlan , 1983Barnes 1988). northern Michigan and Manitoulin Island.…”
Section: H Discussionmentioning
confidence: 99%